2014
DOI: 10.1097/ajp.0000000000000061
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Pain in Traumatic Brain-injured Patients With Different Levels of Consciousness During Common Procedures in the ICU

Abstract: This study support previous findings that critically ill TBI patients could exhibit atypical behaviors when exposed to nociceptive procedures. As such, use of current recommended pain behaviors as part of standardized scales may not be optimal for assessing the analgesic needs of this vulnerable group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 32 publications
2
34
0
Order By: Relevance
“…Furthermore, it is important to further improve tools to make them more sensitive and specific to the detection of pain in critically ill patients with distinct pathologies and differing levels of sedation , Haslam et al 2012, Roulin & Ramelet 2012, Le et al 2013, Arbour et al 2014a,b, Kapoustina et al 2014). This will…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is important to further improve tools to make them more sensitive and specific to the detection of pain in critically ill patients with distinct pathologies and differing levels of sedation , Haslam et al 2012, Roulin & Ramelet 2012, Le et al 2013, Arbour et al 2014a,b, Kapoustina et al 2014). This will…”
Section: Discussionmentioning
confidence: 99%
“…A low effect size was found for the facial expression item of the BPS (Ribeiro et al, 2019) and a grimace score of 2 and muscle rigidity score of 2 on the CPOT were not frequently observed (Joffe, McNulty, Boitor, Marsh, & Gélinas, 2016) raising attention about suitability of these items in this specific ICU population. In alignment with these findings, recent evidence has shown that braininjured ICU patients express unique behaviors (Arbour et al, 2014;Roulin & Ramelet, 2014), and guidelines highlighted the need to revise behavioral pain scales to make their content more suitable to these patients (Barr et al, 2013;Devlin et al, 2018).…”
Section: Introductionmentioning
confidence: 89%
“…The intensive care unit (ICU) admits a wide variety of patients with critical illnesses, all at risk to experience pain either at rest (Chanques et al, 2007) or during standard care procedures (Puntillo et al, 2014). In Canada, the Canadian Institute for Health Information (CIHI, 2007) reports that there are on average 50,000 stroke-related and 23,000 traumatic brain injury (TBI)-related hospitalizations annually.…”
Section: Introductionmentioning
confidence: 99%
“…It is also worth noting that in some groups of ICU patients, the adaptation and validation of behavioral pain assessment tools is still required. Traumatic brain injury ICU patients with altered levels of consciousness show atypical behavioral responses to nociceptive procedures, such as relaxed face, relaxed muscles, sudden eye opening, eye weeping, and limb flexion (49,148). In addition, typical pain behaviors such as grimacing and muscle rigidity (56) were less frequent (49,148).…”
Section: Ethical Considerationsmentioning
confidence: 99%